2020
DOI: 10.1111/caim.12419
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in non‐routine jobs: The role of transformational leadership and organizational identification

Abstract: An increasing number of individuals work in jobs with little standardization and repetition, that is, with high levels of job non‐routinization. At the same time, demands for creativity are high, which raises the question of how employees can use job non‐routinization to develop creativity. Acknowledging the importance of social processes for creativity, we propose that transformational leaders raise feelings of organizational identification in followers and that this form of identification then helps individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
(72 reference statements)
1
16
0
Order By: Relevance
“…Results show that the proposed baseline model fits the data significantly better than several alternative models. This further illustrates that the measurements used in this study have good discriminant validity (Liu et al, 2020).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Results show that the proposed baseline model fits the data significantly better than several alternative models. This further illustrates that the measurements used in this study have good discriminant validity (Liu et al, 2020).…”
Section: Resultssupporting
confidence: 66%
“…First, we used SPSS Version 21.0 and Mplus Version 7.4 to test the reliability of the scales we used in this study. As shown in Table 1, Cronbach's α and composite reliability (CR) of all the four scales were over .80, thereby indicating that these variables have good reliability (Liu et al, 2020). Second, convergent validity (average variance extracted [AVE]) and discriminant validity (Fornell–Larcker criterion) were tested to evaluate the validity by SPSS 21.0 and Mplus 7.4 (Darvishmotevali & Ali, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Creativity is also linked to the person's pursuit of mastery, willingness to take risk, independence and tolerance to various approaches (Beaney, 2019;Benea-Popuşoi, Duca, 2021;Chen et al, 2018;Demarin, Derke, 2020;Jahanshahi et al, 2019;Huertas, Pergentino, 2020;Karimi, et al, 2020). The works of others researchers focus on the relationships between creativity and leadership and, at the same time, between person's self-confidence and self-respect (Fonseca et al, 2019;Hughes et al, 2018;Koh et al, 2019;Liu et al, 2020). The research results also show that creativity is predetermined by the confidence in the power of own efficiency in the society (Haase et al, 2018).…”
Section: Theoretical Bacgroundmentioning
confidence: 89%
“…The study of Hui et al ( 2020 ) on the creativity of millennials also demonstrated that the overlapped identities between self and organization led to the creativity of employees agreeing with the innovation orientation of their organization (i.e., novelty and meaningfulness). Creativity was also captured in multiple levels along with the role of team leaders, job characteristics, and organizational identification (Liu et al, 2021 ). Sætre and Brun ( 2013 ) insightfully interpreted such hierarchies in NPD as a continuous process of creating innovation from top to bottom, or from organization to a final product.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In other words, a team member with high product identification is likely to evaluate the new product favorably, and thus aligned attitudes and/or behaviors can occur more frequently. The empirical study of Liu et al ( 2021 ) demonstrated that organizational identification moderated the positive association between job characteristics and creativity of employees based on a positive feeling and cognitive alignment induced by organizational identification. Few studies on team identification, such as that of Hirst et al ( 2009 ), have also indicated that team identification enhanced the motivation of members to find an aligned self with group goals.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%